Investigation of structural, electrical and optical properties of advanced wide bandgap semiconductor materials and devices - ALMALKI, Abdulaziz (2023)
This thesis reports an investigation of deep level defects in p-i-n Al0.6Ga0.4N/Al0.5Ga0.5N multi quantum wells (MQWs) based deep ultraviolet light emitting diodes (DUV-LED), In0.09Ga0.91N/GaN MQWs based ultraviolet photodetector (UV-PD) and NiO/β-Ga2O3 heterojunction diodes. Firstly, different analytical techniques were used to examine the structural, electrical, and optical properties of AlGaN-based on DUV LEDs with 50% Al content before and after electrical stress process at 100 mA over 150 hours. The cathodoluminescence (CL) intensity of the DUV LED after stress process decreased. Current-voltage (I-V) characteristics demonstrated that leakage current and ideality factor increased from 4.18 × 10-9 cm-3 to 4.50 × 10-9 A and 4.96 to 6.14, respectively ,following electric current stress. Capacitance-voltage (C-V) measurements indicated that the stress process causes the charge carriers to be redistributed in the active region of the MQWs. The Deep Level Transient Spectroscopy (DLTS) measurements at reverse bias VR=-0.5V revealed two and one electron traps with higher concentration in fresh (not subjected to the electrical current process) and stressed (subjected to the electrical current process) LEDs, respectively. Scanning Transmission Electron Microscopy (STEM) images and Energy-Dispersive X-ray (EDX) Spectroscopy mapping showed that there are not many dislocations or defects in the MQWs before electrical stress is applied. As a result of the stress, two dislocation lines appeared and extended throughout the quantum wells.